A Case of Childhood Severe Paroxysmal Cold Hemoglobinuria with Acute Renal Failure Successfully Treated with Plasma Exchange and Eculizumab. (22nd April 2022) - Pelletier, Jessica; Ward, Chad; Borloz, Matthew; Ickes, Anne; Guelich, Susan; Edwards, Erwood
Abstract : We describe the case of a 4-year-old female who presented with sepsis and disseminated intravascular coagulation (DIC), developed ongoing intravascular hemolysis with acute renal failure from suspected pigment-induced acute tubular necrosis necessitating continuous renal replacement therapy (CRRT) for five days followed by four episodes of intermittent hemodialysis (iHD), and was subsequently diagnosed with paroxysmal cold hemoglobinuria (PCH). She was successfully treated with plasma exchange and eculizumab, a humanized monoclonal antibody targeting complement protein C5, and demonstrated significant improvement of hemolysis and recovery of renal function.